Crossing wires: short-circuiting marketing theory. (June 2022) - Coffin, Jack; Eichert, Christian A; Bettany, Shona; Lindridge, Andrew; Oakenfull, Gillian; Ostberg, Jacob; Peñaloza, Lisa; Rinallo, Diego; Rowe, David; Santana, Jannsen; Visconti, Luca M.; Walther, Luciana
In the popular imagination sex sells . Yet, marketing theory has relatively little to say about sexuality per se. Drawing on Žižek's metaphor of critical theory as 'short-circuiting' the dominant discourse, we conceptualise marketing as a field that theorises sexuality only in a series of 'closed circuits'. Knowledge becomes hierarchical when some topics, such as sexuality, are denied the theoretical freedom to roam in wider open circuits alongside other 'mainstream' marketing topics. We identify four ways in which certain topics are enclosed: theoretical, empirical, institutional and neo-colonial. We then seek to short-circuit this state of affairs by bringing together a heterogeneous group of scholars interested in sexuality. By crossing their critical insights like unexpected connections in a circuit, we create sparks of inspiration that challenge the contents, contexts and concepts that relate to marketing theories of sexuality. Our paper makes a specific theoretical contribution in arguing for sexuality to be treated as a phenomenon worth studying and theorising in its own right. However, it also makes a wider methodological and epistemological contribution in showing how various topics within marketing theory might be short-circuited to help flatten the hierarchies of knowledge created by closed and open circuits.